Regulation of NLRP3 by non-coding RNAs in different cancers: interplay between non-coding RNAs and NLRP3 in carcinogenesis and metastasis - Farooqi, Ammad Ahmad; Attar, Rukset; Tanriover, Gamze; Sabitaliyevich, Uteuliyev Yerzhan; Zhailganov, Azamat; Rabandiyarov, Marat (Cellular and Molecular Biology, 2020)
NLRP3 (NOD-, LRR- and pyrin domain-containing protein 3) inflammasomes are multitasking intracellular sensors having characteristically unique ability to detect myriad of microbial motifs and endogenous danger signals which promote structural assembly of NLRP3 inflammasome thus enabling it to perform instrumental roles. Detailed mechanistic insights revealed that molecularly assembled NLRP3 inflammasomes stimulated caspase-1-driven release of the pro-inflammatory cytokines. NLRP3 has been shown to play fundamental role in the regulation of cancer progression and metastasis. Recently emerging cutting-edge research-works have started to shed light on the involvement of non-coding RNAs in the regulation of NLRP3 in different cancers. MicroRNAs, lncRNAs and circular RNAs have been shown to modulate NLRP3 in different diseases. However, we still have incomplete information about regulation of NLRP3 by circular RNAs in various cancers. In this review, we will comprehensively analyze how different microRNAs and long non-coding RNAs modulate NLRP3 in human cancers. Emerging evidence has started to scratch the surface of the participation of miRNAs and lncRNAs in the regulation of NLRP3. Xenografted mice-based studies have also enabled us to develop a better comprehension of interplay between miRNAs, lncRNAs and NLRP3. Hopefully, detailed analysis of contextual regulation of NLRP3 by oncogenic and tumor suppressor miRNAs, lncRNAs and circRNAs will be helpful in getting a step closer to the personalized medicine.